Line outage identification using comparison of bus power mismatch considering PMU outage. (3rd September 2020) - Alam, Mehebub; Kundu, Shubhrajyoti; Thakur, Siddhartha Sankar; Banerjee, Sumit
In this study, a novel algorithm for line outage identification is developed utilising the PMU provided phasor angles. For various outage cases, the simulated bus power mismatches (SBPMs) using bus susceptance matrix of the full network are to be stored. As soon as actual outage occurs, the bus power mismatches are computed using PMU provided pre outage and post outage phasor angles. Additionally, optimal PMU placement issue is also addressed to ensure the network observability in case of PMU outage. Moreover, random Gaussian noise with zero mean and standard deviation (SD) from 1% to 5% is incorporated in the developed model. Simulation was carried out on standard IEEE 5 bus, 14 bus, 30 bus, 57 bus, and 118 bus systems to check the viability and applicability of the proposed methodology. The obtained test results are found to be competitive with the existing methods.